Contribution to the diagnosis of pyelonephritis - Talledo C., Oscar E. (1957)
35 Control: A total of 100 subjects distributed as follows 21 with pyelonephritis was studied as a single diagnosis; 26 with pyelonephritis associated with other processes; TBC 8 kidney and pyelonephritis probable; and 10 with various diagnoses. In finding all the "cells of pyelonephritis" was performed and in most qualitative urine culture done. In 11 no histopathological report. In the control subjects, the finding was negative cells in all. Urine cultures were negative in 2. In subjects with pyelonephritis as a single diagnosis, the cells were found in 95.4%. Urine culture was positive in 94.1% of cases studied. In the group of pyelonephritis associated with other processes, there were cells in the presence of 88.4% and the urine culture was positive in 91.3% of the cases studied. In TBC kidney and pyelonephritis likely cells was found in 87.5%; and 100% of urine was positive. The "diverse" group in any cell was found in 2 of them the urine culture was positive. Of the 45 positive urine cultures, 50% were Escherichia coli; Paracolon gender 27.2%; 15.1% and Staphylococcus Protsus gender; Klebsiella 9.09%; Streptococcus 6.06%; 3.03% Alcalígenos Diphtheroids faecalis and Bacillus and Neisseria 1.01%.